Integrating Co-Curricular Activities with Academic Achievement in Light of NEP 2020 and NCF-SE - Jipsy Malhotra; Rasna Sehrawat; Priyanka S Niranjan (International Journal of Education Sciences, 2025)
This research paper investigates the impact of co-curricular activities on the academic achievement of senior secondary students. The study emphasizes the significance of holistic development in education, where co-curricular activities (CCAs) play a vital role alongside formal academics. CCAs include a range of non-classroom engagements such as debates, music, sports, drama, arts, and community service that contribute to the cognitive, social, emotional, and physical growth of students. These activities are instrumental in breaking academic monotony, fostering adaptability, improving social interactions, and nurturing essential life skills. The study was conducted among 100 Class 11 students (30 boys and 70 girls) in Ghaziabad city. A checklist was used to record participation in 45 co-curricular activities, and academic scores from four core subjects (Science, Mathematics, Language, and Social Science) were collected. Data were analyzed using Pearson’s correlation coefficient and t-tests to determine the relationship between CCA participation and academic performance. The results indicate a significant positive correlation between the level of participation in co-curricular activities and academic performance, especially in Language and Social Science subjects. Girls showed a higher rate of participation and a stronger positive association between CCAs and academic outcomes compared to boys. The findings suggest that co-curricular involvement enhances students’ time management, discipline, motivation, and emotional well-being—factors that contribute directly to better academic performance. While some negative aspects such as over-involvement or poor supervision may exist, the positive impact of CCAs overwhelmingly outweighs these concerns. The study concludes that incorporating structured and inclusive co-curricular programs in school curricula can significantly improve not only academic achievement but also the overall personality development of students. Recommendations are made for educational institutions to formally integrate CCAs to fulfill the NEP 2020 vision of holistic and multidisciplinary learning.
Keywords: Academic Achievement; Co-curricular activities; NEP 2020; holistic development; secondary school students